Social and economic aspects of drift gill net fishing in Guimbal, Iloilo - Defiesta, Gay D.
This study described the socio-economic characteristics of drift gill net owners and assessed the economic performance of the drifts gill net fishing operation. A profile described the living conditions of the owners and costs and returns analysis was used to analyze the economic of the venture. , The research showed the socio-economic characteristics of drift gill net owners describing their age structure, fishing experience, educational attainment, civil status and gender. It also described their housing and household characteristics, emphasizing on household size income, housing materials water supply, fuel and lighting facilities and household conveniences. Costs and returns analysis showed that average total cost in druft gill net fishing was P153.83. Fixed, variable, and opportunity cost accounted for 15.2 percent , 69.38 percent AND 5.5 percent of the total cost respectively. Labor remuneration was P59.10 per trip based on the 50.50 sharing system used by the fishermen. The average catch reported by the fishermen was 5.77 kg. per trip valued at an average price of P27.64. Average revenue per trip was P159.48. Drift gill operators realized an average gross profit of 53.00, financial profit of P29.55 and an economic profit of P5.65.